Comparison of Dental and Skeletal Age Estimating Methods in Children - Özge Çelik Güler; Yeşim Deniz; Semiha Arslan (University of Zagreb. School of Dental Medicine, 2023)
Objectives: Estimating age is a crucial determinant of forensic science. Various methods have been used to estimate dental age (DA) and skeletal age (SA).The aim of the current study was to compare the Cameriere's DA method with the Cameriere's SA method in estimating CA in children. Materials and methods: A total of 216 radiographs of 130 females and 86 males (between 9 to 14.99 years of age) were evaluated in northwestern Turkey. DA was calculated on the panoramic images using Cameriere's open apex method. SA was determined on the lateral cephalograms using the fourth cervical vertebrae method by Cameriere. The DA, SA, and CA data were compared using a paired t-test and Wilcoxon test. Results: The mean CA of all groups was calculated as 12.96±0.30, the mean DA of 12.74±0.68 and the mean SA of 12.89±0.89. In males, the DA method presented an underestimation between ages of 14.00 and 14.99 (p<0.05) and an overestimation between ages 9.00 and 11.99 (p<0.05). In females, the DA method showed an underestimation in the 13.00- and 14.99-year-old age groups (p<0.05) and an overestimation in the 10.00- and 11.99-year-old age groups (p<0.05). The SA method revealed a significant underestimation in females between the ages of 13.00 and 14.99 and in males between the ages of 14.00 and 14.99 (p<0.05). Conclusions: The SA estimation method may provide more accurate results compared to the DA method with children of both sexes aged between 9.00 to 12.99 in the determination of CA.